A modified cyclic crack propagation description. (September 2015) - Dhondt, Guido; Rupp, Michael; Hackenberg, Hans-Peter
Highlights: A multiplicative crack propagation law is proposed including R -effects. The Walker law was extended to take HCF-cycles into account. More than 1000 tests were evaluated to check the new law. The law was applied to steel, Nickel and Titanium alloys. Abstract: A new form of the crack propagation law is presented for cyclic crack propagation calculations. It is characterized by a multiplicative juxtaposition of the Paris range, the threshold and critical limit and the R -dependence. The latter is covered by a modified Walker approach, in which the influence of small cycles at high R -ratios is appropriately adjusted. The concrete form of the R -dependence was validated by application to a wide range of materials.